A new species of Euplocania Enderlein (Psocodea, ‘Psocoptera’, Ptiloneuridae), from the Atlantic Rainforest, Brazil - Silva-Neto, Alberto Moreira da (EntomoBrasilis, 2021)
A new species of Euplocania belonging in the Marginata species group, collected in an area of the Atlantic Rainforest in Brazilian states of Bahia is described and illustrated. It differs from all the other species in the Marginata species group in details of the hypandrium and phallosome. This is the first record of a species in the Marginata species group for the Atlantic Rainforest biome and the first record of a Euplocania species for Brazilian states of Bahia.